Massive epistaxis secondary to an impacted rhinolith in mentally disabled patient - Binti Umar, Nikma Fadlati; Ramli, Ramiza Ramza (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Foreign body nose commonly seen in paediatric age group. In mentally disable patient this may occur and become asymptomatic for many years. We reported mentally disable patient presented with massive epistaxis and history of multiple episodes of foul-smelling discharge from his right nose for the past 20 years. After epistaxis resolved during nasal endoscopy noted impacted rhinolith foreign body in between the septum and the right middle turbinate. Rhinolith successful removed using bent tip of Jobson-Horne probe in otorhinolaryngology, head and neck clinic.